Fontes e doses de NPK em milho irrigado sob plantio direto - Valderrama, Márcio [UNESP]; Buzetti, Salatiér [UNESP]; Benett, Cleiton Gredson Sabin; Andreotti, Marcelo [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (My University, 2011)
Coated fertilizers can provide lower losses and higher soil nutrients availability, which can be absorbed by plants, when we consider their gradual release. The objective of this study was to evaluate the effect of doses and sources of N, P, and K on maize grain components and yield, under no-till system, in the Brazilian savannah. The experimental design was randomized blocks, with 4 top-dressed doses (0 kg ha-1, 40 kg ha-1, 80 kg ha-1, and 120 kg ha-1) and 2 sources (urea and coated urea), for N; 4 doses (0 kg ha-1, 50 kg ha-1, 100 kg ha-1, and 150 kg ha-1) and 2 sources (triple superphosphate and coated triple superphosphate), for P; and 4 doses (0 kg ha-1, 40 kg ha-1, 80 kg ha-1, and 120 kg ha-1) and 2 sources (potassium chloride and coated potassium chloride), for K, with 4 replications. The fertilizers coated with polymers (urea, triple superphosphate, and potassium chloride) were not efficient under the soil and climate conditions studied, because they provided results similar to the same conventional fertilizers, for the N, P, and K foliar contents, and irrigated maize grain components and yield. The increment of N doses increased linearly the N leaf content, number of ears per hectare and maize grains yield. The application of K2O and P2O5 doses did not influence grain yield.
NPK sources and doses on irrigated corn under no-till system
Keywords: Coated fertilizer; Nitrogen fertilization; Phosphorus fertilization; Potassium fertilization; Zea mays L